Proton-electron coupling and mixed conductivity in a hydrogen-bonded coordination polymer - Minju Park; Huiyeong Ju; Joohee Oh; Kwangmin Park; Hyunseob Lim; Seok Min Yoon; Intek Song (Nature Communications)
Abstract The fundamental understanding of coupled proton-electron transport in mixed protonic-electronic conductors (MPECs) remains unexplored in materials science, despite its potential significance within the broader context of mixed ionic-electronic conductors (MIECs) and the possibility of controlled diffusion of protons using hydrogen-bond networks. To address these limitations, we present a hydrogen-bonded coordination polymer Ni-BAND ({[Ni(bpy)(H2O)2(DMF)2](NO3)2·2DMF} n ), which demonstrates high mixed protonic-electronic conductivity at room temperature. Through detailed analysis, we unravel the coupled transport mechanism, offering insights for the rational design of high-performance MPECs. We demonstrate the practical implications of this mechanism by examining the humidity-dependent synaptic plasticity of Ni-BAND, showcasing how MPECs can expand into traditional MIEC applications while leveraging their unique proton-mediated advantages.